The Effect Substitution Of Taro Beneng (Xantoshoma Undipes K. Koch) Flour On The Quality Of Crekers Based On Tapioca Flour - sari syam; Ari Fadiati; Mahdiyah (Jurnal Sains Boga, 2022)
AbstractThe purpose of this study was to analyze the effect of substitution of beneng taro flour (xantoshoma undipes k. koch) on the quality of crackers made from tapioca starch. The independent variable is the number of substitutions made in the manufacture of crackers, with the substitution of taro beneng flour in the manufacture of tapioca crackers and the dependent variable is the physical quality of the crackers. The research was conducted at the Food Processing Laboratory, Catering Education Study Program, Faculty of Engineering, State University of Jakarta from October 2019 to January 2022. This study used an experimental method. This study carried out two assessments, assessing physical quality with aspects of thickness, swellability and oil absorption, and organoleptic quality with aspects that include taste (aroma), color (cracker color and evenness of color) and dryness (dryness level of raw crackers) for raw crackers. For ripe crackers, it includes taste (taste, aroma, umami and trigeminal), color (cracker color, color evenness) and texture (crispy). The physical quality test was repeated 3 times and the organoleptic quality test was carried out on 25 untrained panelists. The results of hypothesis testing using the Anova test with α  = 0.05 showed that there was no effect of substitution of taro beneng flour with different concentrations (30%, 40% and 50%) in making taro beneng crackers on the quality of taro beneng crackers. The recommended formula is taro beneneg crackers with 30% taro flour substitute. Keywords: substitution, crackers, quality, taro beneng